Uso de carbón vegetal activado a partir de madera residual para la utilización en filtros de la planta de tratamiento natural de aguas residuales grises en los molinos Poultier en Latacunga. - Yanchatipan Bustillos, Diego Eduardo (2017)
The present investigation establishes mechanisms to improve the quality of gray water in the natural treatment plant of the Molinos Poultier SA industry located in the city of Latacunga, province of Cotopaxi, through the implementation of activated carbon filters, developing friendly practices with the planet and comply with the environmental legal regulations in force in Ecuador. The research makes a broad study of the subject that contains updated bibliographic review on the use of activated carbon and wastewater. The methodological part makes use of experimental techniques and instruments to determine comparative values of water samples, before and after the use of the filters; finding interesting results [U2], that determine a notable improvement in the quality of gray water. Especially in the PH parameters, the Biological Oxygen Demand (BOD) and the Chemical Oxygen Demand (COD) among others, that determines a discharge of better quality that will serve for irrigation. It is determined that the implementation of activated carbon filters can be replicated in factories with similar characteristics and with positive results.